2006
DOI: 10.1039/b609560g
|View full text |Cite
|
Sign up to set email alerts
|

Studying electron transfer through alkanethiol self-assembled monolayers on a hanging mercury drop electrode using potentiometric measurements

Abstract: A new approach based on measuring the change of the open-circuit potential (OCP) of a hanging mercury drop electrode (HMDE), modified with alkanethiols of different chain length conducted in a solution containing a mixture of Ru(NH3)6(2+) and Ru(NH3)6(3+) is used for studying electron transfer across the monolayer. Following the time dependence of the OCP allowed the extraction of the kinetic parameters, such as the charge transfer resistance (R(ct)) and the electron transfer rate constant (k(et)), for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…The k app values found by us agree well with those reported for DT SAMs coated Au(111) and Au(210) in 1 mM RuðNH 3 Þ 3þ=2þ 6 and 0.1 M NaClO 4 [51]. One order of magnitude greater k app was reported for DT SAMs on a hanging Hg electrode in 0.1 M KNO 3 containing RuðNH 3 Þ 3þ=2þ 6 [52]. The higher value of k app on Hg is probably influenced by its surface properties.…”
Section: Characterization Of Structural Integrity Of Dt Monolayers Bysupporting
confidence: 90%
“…The k app values found by us agree well with those reported for DT SAMs coated Au(111) and Au(210) in 1 mM RuðNH 3 Þ 3þ=2þ 6 and 0.1 M NaClO 4 [51]. One order of magnitude greater k app was reported for DT SAMs on a hanging Hg electrode in 0.1 M KNO 3 containing RuðNH 3 Þ 3þ=2þ 6 [52]. The higher value of k app on Hg is probably influenced by its surface properties.…”
Section: Characterization Of Structural Integrity Of Dt Monolayers Bysupporting
confidence: 90%
“…1.0-1.3 lF/ cm 2 essentially independent of the electrode potential within the potential window of at least 0 to À0.8 V vs. SSCE as reported earlier by several groups [45,52,61,64]. The electron transfer between the hydrophilic redox probes, such as RuðNH 3 Þ 3þ 6 , and the Hg electrode occurs via electron tunneling with the apparent rate constant decaying exponentially with the monolayer thickness (see Eq.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, Mandler used impedance spectroscopy and potentiometric measurements to characterize SAMs on mercury [64,65]. They found that while RuðNH 3 Þ 3þ 6 cannot freely penetrate into the monolayer, the more hydrophobic species, such as CoðbpyÞ 2þ 3 penetrate into the film causing the Fermi level of the Hg surface to attain the Nernst potential of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the alkanethiol monolayer stores charge supplied by the electrochemical potential which imposes a voltage drop across its thickness. The relatively slow electron transfer kinetics attendant electron transfer along the C-C bonded backbone of the alkane chain [10,[43][44][45][46] helps to maintain the potential drop. This effect has been described in detail for several related systems with results varying from nearly complete loss of applied potential to losses of only a few tens of millivolts [43,44,46,47].…”
Section: Discussionmentioning
confidence: 97%